Electronic Commerce 2008
DOI: 10.4018/978-1-59904-943-4.ch061
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation System for IT Outsourcing Customer Satisfaction Using the Analytic Hierarchy Process

Abstract: Many companies have recently been choosing information technology (IT) out-sourcing in response to complicated information systems and various internal requirements. In order to monitor and maintain a high quality of IT outsourcing vendors’ services, it is necessary to develop a system to evaluate IT outsourcing customer satisfaction. The system can be used as a tool for choosing IT outsourcing providers. Through the literature reviews and experts’ interviews, we propose the evaluation system of IT outsourcing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…As for satisfaction, a number of authors have suggested that satisfaction alone is a good measure of success (Kim, Lee, Koo & Nam, 2013;Yoon & Im, 2005, Song & Wong, 2009). The reason may be twofold (Seddon, Cullen & Willcocks, 2007): firstly, it means including and tacitly gauging the costs and benefits implicit in outsourcing; and secondly, satisfaction always constitutes a valid measure, unlike other more specific measures which are not suited to all cases.…”
Section: Satisfactionmentioning
confidence: 99%
See 1 more Smart Citation
“…As for satisfaction, a number of authors have suggested that satisfaction alone is a good measure of success (Kim, Lee, Koo & Nam, 2013;Yoon & Im, 2005, Song & Wong, 2009). The reason may be twofold (Seddon, Cullen & Willcocks, 2007): firstly, it means including and tacitly gauging the costs and benefits implicit in outsourcing; and secondly, satisfaction always constitutes a valid measure, unlike other more specific measures which are not suited to all cases.…”
Section: Satisfactionmentioning
confidence: 99%
“…As for satisfaction, a number of authors have suggested that satisfaction alone is a good measure of success (Kim et al, 2013;Yoon and Im, 2005;Song and Wong, 2009). The reason may be twofold (Seddon et al, 2007): first, it means including…”
Section: Satisfactionmentioning
confidence: 99%
“…AHS 1980 yılında Thomas L. Saaty tarafından ortaya atılan ve çok kriterli karar problemlerinin çözümünde oldukça geniş bir uygulama alanı olan bir yaklaşımdır (Yang ve Huang, 2000;Hafeez vd., 2002;Yoon ve Im, 2005). AHS farklı ölçümlere dayalı (nitel veya nicel) kriter, yargı veya karar alternatiflerini tek bir değerde birleştirip önem açısından sıralamayı amaçlayan ve temel mantığı bu yargıların ikili olarak karşılaştırılması prensibine dayanan matematiksel bir yaklaşımdır (Chin ve Cheng, 2008).…”
Section: Analitik Hiyerarşi Süreci (Ahs)unclassified
“…AHP originally developed by Saaty (1980) is the most common method in the literature about decision making. It is widely implied for obtaining weights of the criteria and alternatives for a variety of research fields and has been implemented in a wide range of studies for many years (Yoon, 2005;Wang et al, 2013;Kutlu et al, 2014;Longaray et al, 2015;Karim and Karmaker, 2016;Tasci and Gorener, 2016;El Haji et al, 2017).…”
Section: Introductionmentioning
confidence: 99%